ORIGINAL PAPER Functional and biopsychosocial restrictions among patients with a venous ulcer - Jawień, Arkadiusz; Szewczyk, Maria T.; Kędziora-Kornatowska, Kornelia; Mościcka, Paulina; Cierzniakowska, Katarzyna; Cwajda, Justyna; Polak, Anna; Grzeszak, Ilona (Archives of Medical Science, 2006)
Introduction: The aim of the study was to assess physical and psychosocial problems of patients with a venous ulcer. Functioning, downfall risk, nutritional status and prevalence of depression were assessed. Relationships between the mentioned variables were also evaluated. Material and methods: The study was conducted in 2004 and 2005 among 77 patients (mean age 73.9, range 55-92), and included 37 patients from the Venous Ulcers Outpatient Clinic of the Chair and Clinic of Surgery and 40 patients from the Chair and Clinic of Geriatrics, Medical University in Bydgoszcz. A short form of the Tinetti test was used for downfall risk assessment, GDS (Geriatric Depression Scale), Mini Nutritional Assessment (MNA) form and III part of EASY-Care 1997-8 questionnaire were used. Results: Patients with an ulcer more often had the following problems: depression (z=5.002, p<0.05), downfall risk (z=3.43, p<0.05), malnutrition (z=3.15, p<0.05) and functional disorders (z=3.37, p<0.05). A higher risk of downfall was observed among patients with functional disorders. The presence of emotional disorders influenced also functioning and nutritional status. Conclusions: Chronic venous insufficiency and ulcers increase the risk of functional disorders in every sphere of patient’s activity – physical, psychological and emotional or social.